WAVE2 2018 Pre-Text Elements and Committees - Gomes, Alex Sandro; Moreira, Fernando Joaquim Lopes; Oliveira, Francisco Kelsen de (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2018: Anais do I Workshop on Advanced Virtual Environments and Education, 2018)
Pre-textual elements and committees of WAVE 2 2018.